Loneliness in people with intellectual and developmental disorders across the lifespan: A systematic review of prevalence and interventions - Alexandra, Petroutsou; Angela, Hassiotis; Ali, Afia (Journal of applied research in intellectual disabilities, 2018)
Background The aim of the study was to conduct the first systematic review investigating the prevalence of loneliness in people with intellectual developmental disabilities (IDD) and the interventions targeting loneliness. Method A search across five databases was conducted (May 2016–June 2016). One reviewer (A. P.) selected the articles for inclusion and assessed their risk of bias using a standardized tool. The second reviewer (A. H.) examined the list of included/excluded articles and the ratings of the studies. Results Five prevalence studies met the inclusion criteria and provided an average loneliness prevalence of 44.74%. Only one intervention study was included, and it demonstrated that there was not any significant group difference for loneliness outcomes (p = .21). The majority of the studies had a weak quality rating. Conclusion The systematic review evidenced that loneliness is a common experience in people with IDD and there is a need to extend current research.